Dekonstruksi Identitas (Neo)Kolonial: Sebuah Agenda Teologi Postkolonial - Putranto, I. Eddy (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2011)
One of the main projects of postcolonial critique has been the recovery of losing or forgotten identity surpassed by colonial power. Postcolonial discourses urge to rescue the colonialized subjects from the trap of colonialized identity. The belief of racial defect lived out by the colonized subjects, for instance, is one of the colonial products accomplished during the time of colonialism. Therefore, deconstruction of colonized identity needs to be done in order to bring the colonized subjects to live in their own history. This postcolonial project should become one of theological agendas today that helps individuals to live confidently in post-colonial time. The urgency of Postcolonial Theology is inevitable especially when we realize that our world is recolonizing, taking in a new way: neocolonialism. Key Words:*Alienation *Boundary *Deconstruction *Home *Hybridity*Imperialism *Inferior *Colonialism *Neocolonialism *Postcolonialism *Subaltern.